2022
DOI: 10.1088/1742-6596/2159/1/012002
|View full text |Cite
|
Sign up to set email alerts
|

Cell lysis analysis for respiratory viruses through simulation modeling

Abstract: An ordinary system of differential equations leading to a simulation model is propose as methodological approach to analysis the incidence of infectious-contagious diseases, in this case using SARS-CoV-2 virus as pathogenic model. The dynamics of the model are drive by the interaction between susceptible cells contemplating respiratory epithelial cells and viral infection mediated by two types of lysis response. To perform the simulations, values of some variables and parameters were selected from referenced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…This work considers two simulation scenarios related to the activation of the immune response against the pathogen SARS-CoV-2; in each scenario, the dynamics of Equation ( 2) are shown, and the parameters were taken from secondary sources [19,[24][25][26][27][28][42][43][44], taking into account that some of these studies suggest that the viral load in the lower respiratory tract is usually undetectable after the onset of symptoms from the second week and approximately between five and fifteen days a decrease in viral load is observed. We clarify that the replication of viral particles can be carried out, as long as both epithelial and infected cells are present within the body.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work considers two simulation scenarios related to the activation of the immune response against the pathogen SARS-CoV-2; in each scenario, the dynamics of Equation ( 2) are shown, and the parameters were taken from secondary sources [19,[24][25][26][27][28][42][43][44], taking into account that some of these studies suggest that the viral load in the lower respiratory tract is usually undetectable after the onset of symptoms from the second week and approximately between five and fifteen days a decrease in viral load is observed. We clarify that the replication of viral particles can be carried out, as long as both epithelial and infected cells are present within the body.…”
Section: Resultsmentioning
confidence: 99%
“…Within the studies of mathematical modeling at the cellular level, many have studied models that include the target cell, the infected cell, and the free virus particles [14,15,19], for example, the dynamics of HIV [20,21], influenza virus, Severe acute respiratory syndrome (SARS) [4,22,23], among others. In addition, the interaction between the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) virus and the immune system has been investigated, where it is possible to explain the dynamics of SARS-CoV-2 within the human host and some immune cells, where it is indicated that approximately between 5 and 15 days after the onset of symptoms is the peak of this response [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%